Potential Role of Adult Stem Cells in Obstructive Sleep Apnea - Almendros, Isaac; Carreras, Alba; Montserrat, Josep M; Gozal, David; Navajas, Daniel; Farre, Ramon (Frontiers in Neurology, 2012)
Adult stem cells are undifferentiated cells that can be mobilized from the bone marrow or other organs, home into injured tissues and differentiate into different cell phenotypes to serve in a repairing capacity. Furthermore, these cells can respond to inflammation and oxidative stress by exhibiting immunomodulatory properties. The protective and reparative roles of mesenchymal stem cells (MSCs), very small embryonic-like stem cells (VSELs) and endothelial progenitor cells (EPCs) have primarily been examined and characterized in auto-immune and cardiovascular diseases. Obstructive sleep apnea (OSA) is a very prevalent disease (4-5% of adult population and 2-3% of children) characterized by an abnormal increase in upper airway collapsibility. Recurrent airway obstructions elicit arterial oxygen desaturations, increased inspiratory efforts and sleep fragmentation, which have been associated with important long-term neurocognitive, metabolic, and cardiovascular consequences. Since inflammation, oxidative stress and endothelial dysfunction are key factors in the development of the morbid consequences of OSA, bone marrow-derived stem cells could be important modulators of the morbid phenotype by affording a protective role. This mini-review is focused on the recent data available on EPCs, VSELs and MSCs in both animal models and patients with OSA.